2018
DOI: 10.1590/s1677-5538.ibju.2017.0632
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 68GA-PSMA PET / CT on treatment of patients with recurrent / metastatic high risk prostate cancer - a multicenter study

Abstract: Purpose:The purpose of our study was to evaluate the clinical impact of 68Ga-PSMA PET / CT in the setting of biochemical recurrence of prostate cancer.Materials and Methods:We retrospectively evaluated 125 prostate cancer patients submitted to the 68Ga-PSMA PET / CT due to biochemical recurrence. The parameters age, Gleason score, PSA levels, and the highest SUVmax were correlated to potential treatment changes. The highest SUVmax values were correlated with age and Gleason score. The median follow-up time was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…Ultimately 16 studies were included in the review (Tab. 2; [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]). Twelve studies reported outcomes using [ 68 Ga]-PSMA-11 PET, while four studies reported data on other PSMA-tracers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately 16 studies were included in the review (Tab. 2; [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]). Twelve studies reported outcomes using [ 68 Ga]-PSMA-11 PET, while four studies reported data on other PSMA-tracers.…”
Section: Resultsmentioning
confidence: 99%
“…Afaq et al found that higher PSA levels were significantly (p = 0.024) associated with management changes; 25.0%, 26.3%, 33.3%, 50.0%, 38.5%, and 50.0% for PSA values <0.2, 0.2-<0.5, 0.5-<1.0, 1.0 < 2.0, 2.0-<5.0, and ≥5.0 ng/ml respectively [38]. Mattiolli et al also found a predictive value of higher PSA levels for change of management (p < 0.0001) [30]. In contrast to these findings, Calais et al found no association between change of management and PSA levels at [ 68 Ga]-PSMA-11 PET/CT [26].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, do clinical decisions change in patients with oligometastatic disease seen in PSMA PET/CT? Table 2 summarizes the results of six retrospective and three prospective studies that observed changes in the management of recurrent PCa following PSMA PET/CT [171819202122232425].…”
Section: Main Bodymentioning
confidence: 99%
“…Gallium-68 ( 68 Ga) and Fluorine-18 ( 18 F)-labeled PSMA tracers are highly effective and show high detection rates, especially in PC patients with biochemical recurrence [ 12 , 13 , 14 ]. Due to its high sensitivity, PSMA-PET/CT helps to stratify patients in primary staging of PC for surgery or for systemic treatment by exclusion or detection of metastases [ 15 , 16 ]. Therefore, PSMA-PET/CT has become the most important imaging modality, especially for staging and restaging of PC.…”
Section: Introductionmentioning
confidence: 99%